Understanding tourist recommendation through destination image: A CHAID analysis - Agapito, Dora (2014)
In spite of the efforts of marketers and managers to boost a favourable destination image, with a focus on encouraging tourists‟ revisit, other factors contribute to tourists‟ decision-making processes with regard to revisiting destinations. Moreover, recommendation from family and friends are considered to be the most credible source of information in the process of choosing a holiday destination, becoming relevant that studies on destination loyalty focus on this variable. Therefore, this research aims to identify the attributes which contribute to tourists‟ willingness to recommend a destination. The first stage of this study involved identifying the attributes to measure the image of Lagos in the Algarve region, an important Portuguese destination, through open-ended questions. In the second phase, the application of the Chi-Square Automatic Interaction Detector (CHAID) to survey responses from a sample of 379 tourists allowed to identify the features that explain the intention to recommend the destination. The results show that culture is the attribute with the strongest power to explain recommendation, highlighting the need for sun and sand tourism destinations to diversify their offer. Of the seven terminal nodes produced by CHAID, two segments with opposite trends were found, for which profiles were drawn.